Iron-Nickel Microparticles in the Sedimentary Rocks as Indicators of Cosmic Processes - R.K. Sungatullin; A.I. Bakhtin; V.A. Tselmovich; G.M. Sungatullina; M.S. Glukhov; Yu.N. Osin; V.V. Vorob’ev (Учёные записки Казанского университета: Серия Естественные науки)
The microstructure, chemical and mineral composition of iron-nickel microparticles from the sedimentary deposits of the Peri-Caspian Depression were studied. It was found that the microspheres developed as a result of the fractional condensation of a Fe-Ni melt and its crystallization at the early stage of the evolution of the substance of the protosolar nebula. Upon reaching the atmosphere of the Earth, these microspheres undergo changes in terms of partial oxidation of magnetite to hematite and native nickel to nickel oxides, melting of fusible metals in the core part, and atmospheric entry under the influence of the “pulverization effect” resulting in the development of awaruite microparticles of various shapes. The obtained data are most likely to prove the extraterrestrial origin of Fe–Ni microparticles and their relation to the fallings of cosmic bodies on the Earth in the geological past.